No rights, no compensation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Building roads can bring new opportunities to remote and poorly developed areas, but for people whose land they cross, they can be very costly. This report covers a road building project in Cameroon, where farmers reacted angrily to a new road, especially as they were not properly compensated for their losses.